Antioxidant and Antidiabetic Activity of Berberis lycium : The Possibilities of TLC-MS Bioautography and in silico Study - Singh, Harjeet; Singh, Nardev (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Since ancient times, the traditional system of medicine has been practiced and developed an array of defense strategies to manage various ailments. About 60-80 percentof people from different parts of the world rely on herbal medicine for their health care. In the present study, a combined method using TLC mass spectrometry bioautography (TLC-MS bioautography) combined with DPPH and α-amylase activities was utilized to compare antioxidant and antidiabetic activities in an aqueous extract of B. lycium. Materials and Methods: In this paper, an aqueous extract of B. lycium was prepared, developed TLC and performed TLC-MS bioautographic to identify the antioxidant and antidiabetic bioactive metabolites. Results: TLC scans were performed at 254 and 366 nm, respectively and obtained results revealed there is a total of 11 and 10 metabolites present in B. lycium. Further, TLC-MS Bioautographic studies isolate a total of two lead compounds such as berberine and palmitine through a chemico-biological detection system. Out of two, berberine showed antioxidant and antidiabetic activity while palmitine only shows antidiabetic activity. Conclusion: TLC-MS bioautographic screening could be an excellent technique to assess the antioxidant and antidiabetic activity of herbal products and the results achieved will be very useful for promoting their utilization and development of new therapeutic regimens.
Keywords: Berberis lycium; TLC-bioautography; Antioxidant; Antidiabetic; in silico